Pengaruh Interaksi Sosial Dalam Penerapan Hukum Islam - Abdul Wasik (IAI Darussalam, 2016)
Fiqh is not the Quran and al-Hadith that we can not change lafadz and its meaning, but Fiqh simply a product and that ijtihad priests schools whose source is taken from the Qur ' and Al-Hadith. Likewise, fiqh is not the doctrine of monotheism filled with doctrine, but it elastic and dynamic in its application. The fall of the Qur'an or better known Asbabun Nuzul and the emergence of Al-Hadith or Asbabul Wurud in Mecca and Medina are very different situations and conditions in Indonesia. Thus, the legal rulings product that was born when the course is also different from the product that appears on the Indonesian fiqh. One reason is the social interaction and the circumstances that exist, thereby causing the product is also different fiqh law